A Socio-Pragmatics Analysis On Promising Utterances In Some Movie Manuscripts - Pudjilestari, Herdini (2012)
This research paper has three problem statements. There are (1) the syntactic form of promising utterances, (2) the intention of promising utterances and (3)the reason of promising utterances. The aims of this research paper are to describe syntactic form, to identify the type of the sentence, to examine the intentions of utterances and to explain the reasons of utterances. The writer employs the descriptive qualitative as the type of the research. The object of the research is promising utternces in How To Train Your Dragon, Kung Fu Panda, I Am Sam, The Next Three Days, Vanilla Sky. The data source of this research is How To Train Your Dragon, Kung Fu Panda, I Am Sam, The Next Three Days, Vanilla Sky, and Swordfish movie manuscripts. The method of collecting the data is observation. The analysis of the type of the sentences is by using Frank's theory. The analysis of the intentions is by using socio-pragmatics and specch act: locution, illocution and the perlocution act. The results of the research paper are: (1) there are three kinds of type of sentence. They are 81,8% of declarative sentences, 13,6% of imperative sentence and 4,5% of interrogative sentence. (2) there are five intentions of the speakers. They are 13,6% of intention to command, 4,5% of intentions to request, 22,8% of intention to assure, 50% of intention to affirm and 13,6 of intention to describe. (3) there are eight reasons of the speakers. They are 22,8% of showing responsibility, 18,2% of showing angry, 13,6 of showing relationship, 4,5% of showing affection, 22,8% of showing hope, 4,5% of showing teasing, 4,5% of showing misunderstanding and 9,2% of showing attention.